A novel approach for enhancing the security of information content of an image. (2018) - Jalesh, Kumar; Nirmala, Shivananda
In this paper, a novel approach is proposed for securing the contents of an image. This approach is a combination of edge detection and encryption process. The proposed approach comprises four stages. In first stage, the input image is divided into blocks of equal size and shuffled. In second stage, the input image is divided into two sub images, image with edges and image without edge information. Canny edge detection algorithm is used for detecting edges in the input image. In third stage, image without edge information obtained from previous stage are encrypted using crossover and mutation operations. The encrypted image and image with edge information are fused in the final stage. The performance of the proposed method is measured in terms of correlation coefficient, histogram and entropy. Different types of attacks are carried out to prove the robustness of the approach. The results obtained are compared with method (Jalesh and Nirmala, 2013). The comparative study reveals that the proposed approach is more efficient to enhance the security of information content of an image.